Analysis of the human health threat caused by the red imported fire ant in mainland China - Huimei Chen; Hongzhi Zhuang; Xiaojing Zhang; Yuling Liang; Mingrong Liang; Yongyue Lu; Lei Wang (PLoS ONE, 2026)
In China, the spread of the red imported fire ant ( Solenopsis invicta Buren, RIFA) exhibits a consistent pattern of expansion from the south to the north, with decreasing severity toward northern regions. The rapid spread of RIFA poses a substantial public health threat in China, particularly in regions where this invasive species has become established. To evaluate the health risks associated with RIFA stings in China, we analyzed the probability of developing various symptoms following RIFA stings using 8,749 representative cases with detailed symptom descriptions recorded between 2004 and 2024. Data were collected from literature reviews, Baidu (a Chinese search platform), and Jinjiang Hospital of Traditional Chinese Medicine. Meanwhile, the potential threat to public health was estimated based on the population density of affected regions in China. The recorded symptoms and their respective occurrence rates were as follows: itching and pain (77.54%), vesicles or pustules (36.12%), urticaria or papules (33.33%), systemic allergy (7.52%), fever (2.65%), dizziness or headache (1.97%), shock (1.17%), localized allergic lymphadenopathy (0.94%), speech impediment (0.75%), and death (0.03%). Based on the distribution, severity, and population density of RIFA in China, it is estimated that approximately 0.6992 million people are likely to be stung annually, including about 0.5422 million experiencing itching and pain, 0.2526 million developing vesicles or pustules, 0.2330 million with urticaria or papules, 526,000 with systemic allergy, 185,000 with fever, 138,000 with dizziness or headache, 82,000 with shock, 66,000 with localized allergic lymphadenopathy, 52,000 with speech impediments, and 209 deaths. RIFA stings can induce symptoms ranging from mild itching and swelling to severe systemic allergy, including anaphylaxis and death, constituting a serious public health concern. Currently, RIFA has spread to more than 700 counties and districts across 13 provinces, endangering the health of approximately 120 million people. Based on current data, an estimated 699,224 individuals may be affected annually, with 8,181 potentially experiencing anaphylactic shock and 209 deaths. There is an urgent need for enhanced protective measures and treatment options. Strengthening monitoring and prevention strategies is critical for mitigating the impact of this invasive species and safeguarding public health in affected regions.